(untitled) (Experimental biology, 2018)
Interspecific interaction between 2 nematodes species – Rhabdias bufonis in lung and Oswaldocruzia filiformis in small intestine we studied by the results of 2015 year field data by morphological measurement. Intestinal nematodes O.filiformis influences to the measurements of lung parasites R.bufonis in more degree: last worms appreciably decreased their absolute sizes in presence of considerable quantity of O.filiformis. Males of O.filiformis almost non-reacted to the number of R.bufonis, females had maximal sizes with middle R.bufonis quantity. R.bufonis decreased their sizes in the presence of large quantity of intestinal nematodes, but lung nematodes had maximal length and width in most numerous semi-populations. Intestinal and lung helminthes are on the different trophy levels: the first consume a part of host’s food, but the second are on the level of predator feeding the tissue (blood). Host’s organism more difficulty restores the lost tissue than the food from gastro-intestinal tract consumed by parasites. Consequently intestinal helminthes which are on the lower trophy level usually significantly limited plastic and energetic requires of tissue parasites than the other way round. The comparison of moor frog nematodes quantity – R.bufonis in lung and O.filiformis in small intestine with separated and together presence in general selection showed that the intestinal nematode had considerable reliable quantitative arranging to the composition of lung parasites. R.bufonis is indifferent to the presence of O.filiformis. In absence of other worm species the quantity of both nematodes species positively arranged each to other. In presence of other parasites O.filiformis had the most gravitation to R.bufonis.